BALATIK: Katutubong Bituin ng mga Pilipino - Ambrosio, Dante L. (Philippine Social Sciences Review; Recent Studies in Philippine History, Eds., Laura Samson and Ricardo Jose, 2010)
Various Philippine cultures have long ago formed their own map of the sky by organizing the stars into constellations. They have, thus, claimed the sky as their own and put their own distinctive marks on it. As they made the sky part of their culture, it in turn, influenced the way they think, act and live. Though the colonial interlude brought changes to Philippine cultures, their high regard for the sky and the stars remained, reinforced and enriched by colonial experience. Balatik and Moroporo are two of the more prominent star groups in the Philippine sky. Philippine cultures have myths that explain the presence of these stars in the sky and their functions in their lives. They consult them as they go on with their everyday lives as in determining the propitious times for planting, fishing and hunting. Together with the sun and the moon, the stars serve as symbols for ideals and values that these cultures hold on to.